Subinteger Range-Bin Alignment Method for ISAR Imaging of Noncooperative Targets. (2010) - Muñoz-Ferreras Muñoz-Ferreras, J. M. J. M.; Pérez-Martínez Pérez-Martínez, F. F.
Abstract : Inverse Synthetic Aperture Radar (ISAR) is a coherent radar technique capable of generating images of noncooperative targets. ISAR may have better performance in adverse meteorological conditions than traditional imaging sensors. Unfortunately, ISAR images are usually blurred because of the relative motion between radar and target. To improve the quality of ISAR products, motion compensation is necessary. In this context, range-bin alignment is the first step for translational motion compensation. In this paper, we propose a subinteger range-bin alignment method based on envelope correlation and reference profiles. The technique, which makes use of a carefully designed optimization stage, is robust against noise, clutter, target scintillation, and error accumulation. It provides us with very fine translational motion compensation. Comparisons with state-of-the-art range-bin alignment methods are included and advantages of the proposal are highlighted. Simulated and live data from a high-resolution linear-frequency-modulated continuous-wave radar are included to perform the pertinent comparisons.